The anthropology of Hilary of Poitiers - Image, I (2014)
This thesis examines the theological of the fourth-century bishop, Hilary of Poitiers, concentrating particularly on two commentaries written at different times in his life. The thesis starts by examining the texts, and demonstrates that Hilary's commentary on Psalm 118 is loosely speaking a translation of Origen; by comparing both authors with Ambrose, the relationship between Origen and Hilary appears much closer than previously thought. The main body of the thesis examines Hilary's anthropological theology. Three chapters look at created human nature, looking at the relationship between body and soul, human nature as imago dei, and the extent to which human nature can be treated as a platonic universal. The general conclusion is that Hilary is not particularly platonic, and at this stage is not particularly stoic either, but rather is eclectic in his choice of philosophical ideas. The influence of Origen is clear but Hilary only uses Origen’s theology critically. There follow four chapters on the Fall and its impact, focussing particularly on its effects on human nature. In particular it is shown that Hilary presages Augustine's teaching of the fallen will; in Hilary the Will is described as being in thrall to her mother-in-law Disobedience. Another human malady is the effect of the passions or emotions, where Hilary is influenced by Stoic ideas of the process of human action; nevertheless, concepts such as apatheia or the propatheiai do not appear in his work. These constraints on human action point towards Hilary's theology of original sin; indeed he appears to be the first author to use the phrase peccata originis in this sense. In the concluding chapter, Hilary's place in the continuum between Origen and Augustine is demonstrated; at very least, original sin cannot be called an African doctrine, since it first is named by Hilary, a Gaul.